Bounds Estimation for Trade Openness and Government Expenditure Nexus of ASEAN-4 Countries - Kueh, Jerome Swee Hui; Puah, Chin-Hong; Wong, Chiew-Meu (Universiti Malaysia Sarawak, 2014)
Southeast Asia countries are encountering several challenges as they are moving towards the globalization and trade liberalization era. Due to that, government intervention is essential in ensuring that the economy is resilience against the severe implications of trade openness. Therefore, this study aims to examine the relationship between trade openness and government expenditure of ASEAN-4 countries using the Autoregressive Distributed Lag [ARDL] bounds testing approach that covers a sample period of annually data from 1974-2006. Empirical results indicate that there is an existence of a significant positive long-run linkage between trade openness and government expenditure of all the ASEAN-4 countries under study. This means that government intervention in an open economy is crucial as to cushion the risks associated with trade liberalization.